Leadership entrepreneur dan intellectual capital terhadap kinerja keuangan BUMDes: Innovation capability sebagai pemoderasi - Kusumawardani, Niken; Susi, Susi; Sukmasari, Dewi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study examines the effect of entrepreneurial leadership and intellectual capital on the financial performance of village enterprises (BUMDes) through innovation capability. The independent variables in this study are entrepreneurial leadership (X1) and intellectual capital (X2), the dependent variable is financial performance (Y), and the moderating variable is innovation capability (Z). Methodology: The sample in this study was BUMDe officials at the Pesawaran Regency Government. Data were collected using a questionnaire and processed using the statistical regression test in SPSS. Results: The results show a significant relationship between entrepreneurial leadership and intellectual capital on financial performance, and innovation capability can moderate the financial performance variable. Limitation: This study only refers to one district in Lampung Province and data was only provide Contribution: The results of this study are expected to present an overview of officials and policymakers regarding the importance of innovation in managing BUMDes operations.